Study of Charge Density Distributions, Elastic and Inelastic Electron Scattering Form Factors and Size Radii for 24Mg and 28Si Nuclei - M. Abbas, Zaid; N. Flaiyh, Ghaith (Al-Nahrain Journal of Science, 2025)
Unitary Correlation Operator Method (UCOM) has been used to inspect the ground state properties of 24Mg and 28Si nuclei, such as, charge densities, the root mean square () radii and elastic electron scattering form factors. Inelastic longitudinal electron scattering form factors have been computed for iso scalar or transition ∆T=0 of the () and (  transitions) for the 24Mg and 28Si nuclei. The results of the computations have been discussed, and a comparison of those results with the experimental data has occurred. It was assured that the unitary correlation operator method is suitable for studying the nuclear structure.